Biaryls as potent, tunable dual neurokinin 1 receptor antagonists and serotonin transporter inhibitors. Issue 15 (1st August 2015) - Degnan, Andrew P.; Tora, George O.; Han, Ying; Rajamani, Ramkumar; Bertekap, Robert; Krause, Rudolph; Davis, Carl D.; Hu, Joanna; Morgan, Daniel; Taylor, Sarah J.; Krause, Kelly; Li, Yu-Wen; et al.
Graphical abstract